First report of Patagonian toothfish (Dissostichus eleginoides) metabolic rate and its scaling on a surface culture system - F. Encina-Montoya; R. Vega-Aguayo; C. Oberti-Grassau; A. Mardones-Lazcano; G. Muñoz; R. Barrios-Figueroa; C. Alvarado-Flores; A. Reyes-Campos; M. A. Urbina-Foneron (Brazilian Journal of Biology)
Abstract Dissostichus eleginoides is a benthopelagic, carnivorous fish from circumpolar antarctic waters. It is a deep sea fish distributed up to 2500 m and reaching up to 200 kg, 2 m total length and over 50 years of lifespan. Although it is of commercial interest, with prices between 14-35 US$/kg, studies that allow its cultivation are scarce. D. eleginoides is considered to have a slow metabolism since it lives at low temperatures (2-11 °C) and high pressures (100-250 atmospheres). However, there are no records of their routine aerobic metabolism (or any in fact) and of their mass scaling in tanks captivity on the surface, being the aims of this study. Routine metabolism was measured in fish groups from 3 sizes, a) 2.31 ± 0.08 kg, b) 4.67 ± 0.06 kg and c) 8.97 ± 1.89 kg in two respirometry chambers allowing to perform closed respirometry. The average metabolic rate was 42.91 ± 0.48, 38.61 ± 2.64 and 35.35 ± 1.58 mg O2 kg-1 h-1 along fish sizes, with significant differences between sizes. The calculated scaling exponent was 0.85, similar to that reported for other cold-water fish species measured at the surface. Results show oxygen consumption rates, under surface pressure conditions, comparable to those of G. morhua and salmonids, which allows, preliminarily, to reject the initial hypothesis of a slow metabolism. Although the results are preliminary, they are the first to report on the routine metabolism of this species, making them relevant for future studies. Culture densities of 87.38, 57.77 and 64.92 kg m-3 were estimated for groups a, b and c presenting important advantages and new perspectives for the cultivation of D. eleginoides.